2016
DOI: 10.1007/s10614-016-9610-3
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Model of Unemployment with Migration and Delayed Policy Intervention

Abstract: The purpose of this paper is to build and analyse a model of unemployment, where jobs search is open to both natives and migrant workers. Markets and government intervention respond jointly to unemployment when creating new jobs. Full employment of resources is the focal point of policy action, stimulating vacancy creation. We acknowledge that policy is implemented with delays, and capture labour market outcomes by building a non-linear dynamic system. We observe jobs separation and matching, and extend our mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Besides, they discovered that the unemployment level was signal to the employers to hire labourers at low wages. The separation of the available vacancies into government and current created vacancies was a major modification to the earlier works of Misra and Singh (2011) and Misra and Singh (2013) by Harding and Neamtu (2018). Harding and Neamtu adopted the idea of Misra and Singh (2011) and Misra and Singh (2013), modifying the earlier efforts by formulating an unemployment model in which job searches are open to both migrant and native workers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, they discovered that the unemployment level was signal to the employers to hire labourers at low wages. The separation of the available vacancies into government and current created vacancies was a major modification to the earlier works of Misra and Singh (2011) and Misra and Singh (2013) by Harding and Neamtu (2018). Harding and Neamtu adopted the idea of Misra and Singh (2011) and Misra and Singh (2013), modifying the earlier efforts by formulating an unemployment model in which job searches are open to both migrant and native workers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Set a ∼ Normal(2, 1) and b ∼ Gamma(2, 2). Let g(t) = sin(dt 2 ), where d ∼ Beta (10,9). We know that φ a (ζ) < ∞ for all ζ ∈ R, and that b has centered absolute moments of any order.…”
Section: Theorem 32 (Existence and Uniqueness)mentioning
confidence: 99%
“…In particular, delays play a key role in Biomathematics (population dynamics, infectious diseases, physiology, biotic population, immunology, neural networks and cell kinetics) [4][5][6], but also in other realms like Chemistry [7,Ch. 4], Engineering [8], Economics and Finance [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it is shown that avenues for skill development play an important role to control unemployment. Taking the concept from Misra and Singh [10,11], Harding and Neamtu [6] proposed a continuously distributed delay mathematical model to study the problem of unemployment in a country, where both natives and migrant unemployed persons search for jobs.…”
Section: Introductionmentioning
confidence: 99%